2017
DOI: 10.21037/atm.2017.01.37
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound to assess diaphragmatic function in the critically ill—a critical perspective

Abstract: Ultrasound of the diaphragm in critically ill patients has become a diagnostic technique of emerging interest among clinicians and scientists. The advantages include that it is widely available, noninvasive and examination can be performed after relatively short training and at low costs. It is used to estimate muscle mass by measurement of muscle thickness and diagnose weakness by the assessment of diaphragm movement during unassisted breathing. Thickening of the muscle during inspiration has been used to qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The use of diaphragm ultrasound is growing in the ICU [ 28 , 29 ]. It has many advantages over phrenic nerve stimulation, which requires costly equipment and extensive technical expertise.…”
Section: Discussionmentioning
confidence: 99%
“…The use of diaphragm ultrasound is growing in the ICU [ 28 , 29 ]. It has many advantages over phrenic nerve stimulation, which requires costly equipment and extensive technical expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound has gained in popularity as a diagnostic tool in clinical management and research in the ICU (14). The role of ultrasound to evaluate respiratory muscle function and effort have been discussed in recent articles (65,73). Components of the respiratory muscle pump, including the diaphragm, abdominal wall muscles and accessory muscles, are positioned relatively superficial and are readily accessible for ultrasound.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Advantages of ultrasound include the non-invasive nature, low-costs, steep learning curve and straightforward calculations which allows bedside evaluation of breathing effort (73). However, several technical and methodological limitations apply to ultrasound assessment of breathing effort.…”
Section: Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the use of POCUS in evaluating diaphragm functionality is of interest. Research has shown that the use of POCUS to measure diaphragm thickness, motion and thickening fraction can quantify diaphragm atrophy and predict weaning success (7,8).…”
mentioning
confidence: 99%